Open Seminar on Acoustics OSA'2006 - Engel, Zbigniew; Wiciak, Jerzy (Archives of Acoustics, 2006)
It is our pleasure to offer you papers submitted at the 53rd Open Seminar on AcousticsOSA’06 that was held in the charm and beautiful city of Zakopane, the highestlocated city in Poland, from September 11 to 15, 2006. The conference was organizedjointly by the Polish Acoustical Society, Kraków Division, Committee of Acoustics,Polish Academy of Sciences and Department of Mechanics and Vibroacoutis, Facultyof Mechanical Engineering and Robotics at the AGH University of Science and Technology.The conference was attended by 160 scientists from Poland. There were 9 plenarylectures and over 120 contributed lectures. We continued with the tradition of posterpresentation session to provide the maximum participation.This volume represents the diversity of contributions to the conference. We distinguished11 different aspects of theoretical and experimental research in the field ofacoustics. The papers are organized in an alphabetic order according to these topics:• biomedical acoustics• physical acoustics,• molecular and opto acoustics,• speech acoustics,• musical acoustics,• room acoustics,• environmental acoustics,• electroacoustics,• hydroacoustics,• transducers,• psychoacoustics.The Archives of Acoustics has developed a regular peer review system in the selectionof submitted papers. The Organizing Committee has sought advice from tworeviewers who are knowledgeable in the subject of the paper.We wish to express our special thanks to the referees for their active interest in thepublishing of this book. We want also to thank the authors for preparing and correctingthe manuscripts so that the most manuscripts were in acceptable form one month afterthe conference.We hope that these publications will be of interest of everyone and meet the expectationsof the readers.